Assembling bodies art, science & imagination ; [... exhibition, march 2009 - november 2010, Museum of Archaeology and Anthropology, University of Cambridge] - Herle, Anita; Elliott, Mark W.; Empson, Rebecca M. (Museum of Archaeolog and Anthropology, 2009)
Literaturverz. S. 95 - 96
Keywords: Körper -- Motiv; Körperbild; Body Art; Körpererfahrung; Ausstellungskatalog -- 2009-2010 -- Cambridge; Konferenzschrift